2021
DOI: 10.3390/biology10080759
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Foot: The Role of Fasciae, a Narrative Review

Abstract: Wound healing is an intricate, dynamic process, in which various elements such as hyperglycemia, neuropathy, blood supply, matrix turnover, wound contraction, and the microbiome all have a role in this “out of tune” diabetic complex symphony, particularly noticeable in the complications of diabetic foot. Recently it was demonstrated that the fasciae have a crucial role in proprioception, muscular force transmission, skin vascularization and tropism, and wound healing. Indeed, the fasciae are a dynamic multifac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 80 publications
3
16
0
Order By: Relevance
“…Daleswski et al [ 22 ] studied the COL5A1 rs12722 and rs13946 polymorphisms as potential genetic factors regulating the ADDwoR-mediated soft tissue pathway in association with temporomandibular joint anterior disc displacement [ 22 ]. Pirri et al [ 46 ] reported that:” excessive aggregation of ECM elements is present in fibrosis (e.g., in myopathies), including in fasciae, and occurs during aging [ 16 ], and diabetes, characterized by increased endomysium as well as perimysium” [ 47 ]. Diet-induced insulin resistance (IR) leads to an increase in the expression of collagens I, III, and IV [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Daleswski et al [ 22 ] studied the COL5A1 rs12722 and rs13946 polymorphisms as potential genetic factors regulating the ADDwoR-mediated soft tissue pathway in association with temporomandibular joint anterior disc displacement [ 22 ]. Pirri et al [ 46 ] reported that:” excessive aggregation of ECM elements is present in fibrosis (e.g., in myopathies), including in fasciae, and occurs during aging [ 16 ], and diabetes, characterized by increased endomysium as well as perimysium” [ 47 ]. Diet-induced insulin resistance (IR) leads to an increase in the expression of collagens I, III, and IV [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory analyses revealed a microcytic anemia (Hb 118 g/L, MCV 78 fL), leukocytosis (13x109/L) and elevated value of C-reactive protein (45. 6 CM, the most frequent primary tumor in adults, commonly occurs in the left atrium; its occurrence on the valves is extremely rare [1]. The patients may present with 1) symptoms or signs of mechanical outflow tract obstruction in about 60% of the patients, imitating clinical presentation of valve stenosis, 2) general/ constitutional signs and symptoms and laboratory abnormalities in 10-45% of patients and 3) embolization of the tumor fragments or thrombus adherent on the tumor surface in the 30-40% of cases [1].…”
Section: To the Editormentioning
confidence: 99%
“…In this case, substantial US imaging (including sonopalpation) uncovered the exact pain generator in the subcutaneous tissues including superficial fasciae [1,3]. Accordingly, prompt management was done with in-depth understanding of the symptomatology and tissue biomechanics, as well as targeted intervention whereby reorganization of the subcutaneous tissue caused mechanical stress on the fascial layers, triggering inflammation and stiffness during the healing process [4][5][6].…”
Section: To the Editormentioning
confidence: 99%
“…Based on histological properties and anatomical relationships, fascia may be classified into four types: superficial (subcutaneous) fascia, deep/muscular fasciae (aponeurotic and epimysial fasciae), visceral fasciae, and neural fasciae (meningeal layers and connective tissue sheath of peripheral nerves) [ 4 , 5 ]. Structurally the fascia tissue consists of various cell types (fibroblasts, myofibroblasts, fasciacytes, and telocytes), an extracellular matrix consisting of fibrous (types I and III collagen fibers, elastin, and fibrillin), and aqueous (water and complex mixture of glycosaminoglycans) components, and nerve elements (free nerve endings and mechanoreceptors) [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deepening our understanding of the microanatomical and biochemical basis of fascial disease in obesity may provide novel therapeutic insights for the medical and surgical treatment of obesity-related myofascial complications. A significant body of evidence has highlighted the critical role of fascial cells, extracellular matrix, and nerve elements in the pathogenesis of myofascial disease [ 4 , 6 ]. In this regard, a therapeutically relevant consideration is the role of hyaluronan (hyaluronic acid) in clinical fasciopathy.…”
Section: Introductionmentioning
confidence: 99%